How Satisfied are the English Major Students with their Foundation English Courses: An Appraisal - Dr. Usha Sadasivan (University of Chitral Journal of Linguistics and Literature, 2020)
This study aims to investigate and evaluate the level of satisfaction of the English major students with their foundation English course. To this end, a questionnaire was administered to both the students who are currently pursuing the course and the students who had completed the course. The motive was to compare the results of the two sets of responses to see if both sets of students felt the same regarding the foundation English curriculum. The questionnaire was self-administered, through Google forms. The study threw light on the responsibilities of educational institutions in understanding that higher education is a service industry. It also highlighted the need for educational institutions to realize that they need to satisfy needs and the expectations of students, parents and employers. These three are the main stakeholders in the education industry today. Syllabus framers too have to accept that changes are imminent and make more than cosmetic changes to accommodate changes in the world outside. Students should be roped into the curriculum framing committees as they know what they need and what is not being delivered to them. Giving importance to aspirations of students is unavoidable. It is hoped that this study would throw light on the expectations of students so that necessary changes may be made in the curriculum and thereby bring about the desired learning outcomes.